Full robot-assisted gastrectomy: surgical technique and preliminary experience from a single center. Issue 4 (December 2016) - Quijano, Yolanda; Vicente, Emilio; Ielpo, Benedetto; Duran, Hipolito; Diaz, Eduardo; Fabra, Isabel; Malave, Luis; Ferri, Valentina; Ferronetti, Antonio; Plaza, Carlos; D'Andrea, Vito; Caruso, Riccardo
Abstract The treatment of gastric cancer requires a multidisciplinary approach in which surgery plays the main role. The diffusion of minimally invasive surgery for gastric cancer treatment is limited by the complexity of performing an extended lymphadenectomy. This surgical step can be facilitated through the use of a robot-assisted system. To date, there are few published articles discussing a full robotic approach that precisely show the different surgical steps. The aim of this study is to describe our experience, surgical techniques and the short-term results of a consecutive series of full robotic gastrectomies using the Da Vinci Surgical System. From November 2011 to January 2015, 17 patients with gastric cancer underwent curative resection by robotic approach for locally advanced tumors. In summary, there were 15 total gastrectomies with a Roux-en-Y esophagojejunostomy, one total gastrectomy with transverse colectomy and one sub-total gastrectomy. Resection margins were negative in all cases. Conversions occurred in two patients. Robot-assisted gastrectomy with extended lymphadenectomy is a safe technique and successfully allows an adequate lymph node harvest and optimal R0-resection rates with low postoperative morbidity. The learning curve appears to be shorter than in laparoscopic surgery. Further follow-up and randomized clinical trials are required to confirm the role of a robotic approach in gastric cancer surgery.